Od winiarni Briegera do cerkwi greckokatolickiej = From Brieger`s winery to greek orthodox church - Wanatko, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Zielona Góra has a flourishing tradition of the production of wine. The city itself reminds us about it in many objects. One of them is the building of a former winery of Fritz Brieger. This marchant and wine pro?ducer built it in 1880. After his death in 1918, his niece Martha Gischke was looking after the winery. In the interwar period its status was changed, but the profiel of production remained the same, such as the name of company.
Keywords: Winiarnia Fritza Briegera; Marczyński, Stanisław; Wytwórnia Win Antoni Kulesza; Lubuska Wytwórnia Win; grekokatolicy; Zielona Góra; Fritz Brieger Wine House; Antoni Kulesza Wine Factory; Lubuskie Wine Factory; Greek Catholic Church